2001
DOI: 10.1103/physrevb.64.245326
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian theory of the composite-fermion Wigner crystal

Abstract: Experimental results indicating the existence of the high magnetic field Predictions for gaps and the shear modulus of the crystal are presented, and found to be in reasonable agreement with experiments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…The results, together with other variational studies [27], supported the interpretation of the observed HFIPs and RIPs as pinned WCs. However, the liquid-WC transition phase diagram remains unsettled [28,29], especially in the range from ν=1 to the B=0 limit, since a reentrant WC that was expected at ν >1 (Ref. 26(b)) has never been observed experimentally.…”
mentioning
confidence: 99%
“…The results, together with other variational studies [27], supported the interpretation of the observed HFIPs and RIPs as pinned WCs. However, the liquid-WC transition phase diagram remains unsettled [28,29], especially in the range from ν=1 to the B=0 limit, since a reentrant WC that was expected at ν >1 (Ref. 26(b)) has never been observed experimentally.…”
mentioning
confidence: 99%
“…and as such is evidence for CF interaction. FQHEs of interacting CFs have been observed [6] as well, and CF Wigner solids have been considered theoretically [23][24][25] for low electron Landau fillings. Changing ν = 1/3 ± 0.015 to CF filling results in ν CF = 1 ± 0.15.…”
mentioning
confidence: 99%
“…the actual ground state is a type-I CFWC. [10][11][12][13][14] Essentially, electrons capture fewer than the maximum number of vortices available to them, and use the remaining degrees of freedom to form a WC. The CFWC has been shown to be an excellent approximation of the exact state in numerical diagonalization studies.…”
Section: Introductionmentioning
confidence: 99%